VAT compliance and the influence of political and business environment: a proposed framework for Nigerian SMEs - Nura, Mohammed; Abdul Jabbar, Hijattulah; Ibrahim, Idawati (IDOSI Publications, 2017)
Oil producing country like Nigeria, for so long has depends largely on petroleum profit tax revenue and seem knowingly had less emphasised on taxes from non-oil sources. However, recent worldwide dropped in the oil prices, which continually lower the tax revenue, alerted the government to consider tax policy decision and administration of non-oil tax revenue. This article focuses on Value Added Tax (VAT) as the available data indicating an alarming trend about VAT noncompliance, especially the small and medium enterprises. Factors that influence compliance behaviour are numerous and derived from various theory and models However, the majority of the studies on factors determing tax compliance concentrated mainly on income tax. By utilising the economics deterrence model, this paper discusses and proposes a VAT compliance framework that incorporates the political environment and business environment as determinants of VAT compliance behaviour in the Nigerian context.